Geopolitical Reflections of Sino-Indian Conflict and its Implication on Nepal’s Survival Strategy - Bhattarai, Gaurav (Unity Journal, 2021)
Border disputes between China and India in June 2020 almost lead South Asian countries to take a side. But, Nepal, situated between India and China, has always expressed a stern belief in neutrality and non-alignment. Even though New Delhi doubted Nepal’s neutrality and non-alignment citing China’s growing footprints in Nepal, Kathmandu reckoned such suspicion as the result of a new map row between two countries connected by open borders. While Nepal’s repeated calls to diplomatically resolve India-Nepal border problems remained unheeded by New Delhi, it provided room for the ruling communist party in Nepal to reap geopolitical benefits out of the Sino-Indian dispute. But, interestingly, such geopolitical benefits are usually targeted in tempering Indian influence in Nepal, by getting closer with China. Apprehending the same, this study aims to assess the geopolitical implication of Sino-Indian conflict on the survival strategy of Nepal. To fulfill the same objectives, the Chinese perception of Nepal-India relations, and Indian perception of Sino-Nepal ties have been critically assessed in this study. This study is methodologically based on the information collected from the secondary sources. In order to critically evaluate the geopolitical expression of Sino-Indian conflict in Nepal, this study reviews India’s perception of Nepal-China relations, and China’s perception of Nepal-India relations. Also, the reports and the press releases of the Ministry of Foreign Affairs, historical facts, treaties, government reports and decisions have been studied and analyzed. Media sources are also reviewed to understand the diverse narratives produced on the geopolitical reflection of Sino-Indian conflict. The themes that emerged from the reviews are thematically analyzed and interpreted, to discover that cultivating relations with one country at the expense of the other may be counterproductive to Nepal’s survival strategies.